Addressing blood-brain-tumor-barrier heterogeneity in pediatric brain tumors with innovative preclinical models - Morris, Elysse K.; Daignault-Mill, Sheena; Stehbens, Samantha J.; Genovesi, Laura A.; Lagendijk, Anne K. (Frontiers in Oncology, 2023)
Brain tumors represent the leading cause of disease-related mortality and morbidity in children, with effective treatments urgently required. One contributing factor to the effectiveness of systemic therapy is the blood-brain-barrier (BBB), which limits the brain penetration of many anticancer drugs. BBB integrity is often compromised in tumors, referred to as the blood-brain-tumor-barrier (BBTB), and the impact of a compromised BBTB on the therapeutic sensitivity of brain tumors has been clearly shown for a few selected agents. However, the heterogeneity of barrier alteration observed within a single tumor and across distinct pediatric tumor types represents an additional challenge. Herein, we discuss what is known regarding the heterogeneity of tumor-associated vasculature in pediatric brain tumors. We discuss innovative and complementary preclinical model systems that will facilitate real-time functional analyses of BBTB for all pediatric brain tumor types. We believe a broader use of these preclinical models will enable us to develop a greater understanding of the processes underlying tumor-associated vasculature formation and ultimately more efficacious treatment options.